Rethinking Consumer Legal Remedies for Damaged Goods Under Protection Fees on E-Commerce Platforms: The Shopee Case Study - Manggala, Ferdiansyah Putra; Susanti, Dyah Ochtorina (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
Over time, globalization has brought significant advancements in technology, especially in e-commerce. In the past, transactions were carried out offline, but with the advent of e-commerce, transactions can now be done online. One such e-commerce application is Shopee, which originated in Singapore and has expanded to countries such as Indonesia. Shopee has introduced a new feature called protection fees. Protection costs are the costs associated with protecting the buyer in the event of damage, subject to certain terms and conditions. However, the cost of protection has become a concern for consumers because they do not receive the compensation to which they are entitled. The research method used in this study is normative legal research. The results of the study show that legal protection for consumers related to damage claims that are subject to protection fees on the Shopee application can be categorized into two forms: internal legal protection based on agreements and external legal protection based on the Consumer Protection Law and the Insurance Law. Dispute resolution for consumers based on Article 45 of the Consumer Protection Law can be pursued through two methods: non-litigation and litigation. The non-litigation method involves resolving external disputes through the Consumer Dispute Resolution Institution (BPSK) using mediation. If an agreement is not reached, litigation can proceed through legal channels, with consumers filing lawsuits based on breach of contract.